Bioaccumulation Monitoring of Heavy Metal Chromium (Cr) in Fish Oreochromis mossambicus in The Floating Net Cultivation in Sidoarjo Krembangan River - sonny kristianto (Hasanuddin University, 2018)
ABSTRACTFloating Net is a simple alternative cultivation methods. The river there is a garden in the Krembangan District Sidarjoi which is used as a place of cultivation of Floating net fish oreochromis mossambicus (Oreochromis mossambicus), on the other hand is where waste disposal by the local community and some industries . This research aims to know the accumulation of heavy metals chromium (Cr) in the flesh of fish oreochromis mossambicus (Oreochromis mossambicus) and find out the feasibility of fish consumption oreochromis mossambicus at floating net on the river Krembangan Sidoaarjo. This research are observatif by using Purposive Random Sampling techniques. test the content of heavy metal chromium (Cr) in the flesh of fish oreochromis mossambicus (Oreochromis mossambicus) method using AAS (Atomic Absorbtion Spectrofotometry). The data generated in the analysis in quantitative descriptive. In this research show that the heavy metal content of chromium (Cr) in the flesh of fish oreochromis mossambicus highs station III of 0.52 mg/Kg; I station of 0.51 mg/Kg II station of 0.48 mg/Kg on a sampling sedangkang the morning, at night the highest value on the station III of 0.50 mg/Kg; I station of 0.46 mg/Kg and the II of 0.39 mg/Kg. Average deposits of heavy metal Cr on fish oreochromis mossambicus (o. mossambicus) is still under the raw quality of the already established by the Director-General of POM 1989 i.e. amounted to 2.5 mg/kg but fall into the category bioakumulasi medium, so that fish oreochromis mossambicus is still worthy of consumption, but need to watch out for, considering the Cr are toxic, carcinogenic, bioakumulatif and biomagnifikasi would potentially interfere with health.